NEGOTIATING AGEING IN A CHANGING INTERGENERATIONAL LANDSCAPE. (11th November 2018) - Biggs, S
Abstract: The demographics of population ageing are well known, yet cultural adaptation has been slow to gain momentum beyond notions of continuing to stay as one is- either in terms of continued working, midifestyle consumption or resisting changing lifecourse priorities. It is suggested that cultural adaptation contain at least two principal challenges: finding novel purpose and contribution from a long life that are connected to changing lifecourse priorities and negotiating a situation where generational groups are becoming approximately the same size. A numberof tensions will be examined as a means of interrogating this novel landscape: between positive and negative forms of discontinuity, positive forms of othering, within-age and between-age thinking, and, present and lifecourse centred perspectives. Implications social policy and intergenerational relationships will be explored.